2001
DOI: 10.1007/s004210100457
|View full text |Cite
|
Sign up to set email alerts
|

Is breath-hold time an objective index of exertional dyspnoea in humans?

Abstract: Since dyspnoeic sensation (d) increases progressively with work rate (WR) and the duration of a volitional breath-hold (t BH ) shortens, we wished to explore whether t BH might correlate suciently closely with d to provide a quantitative and descriptor-free index of respiratory sensation during dynamic exercise. Nine healthy males exercised on a cycle ergometer at a series of constant WRs, above and below the lactate threshold. Ventilatory and gas exchange variables were measured breath-by-breath. At each WR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Increasing metabolic rate also shortens breath‐hold duration (Rodbard, 1947; Cummings, 1962; Lin et al 1974; Ward et al 2001). Figure 4 shows that exercise (bicycle ergometry to at least double metabolic rate) more than halved breath‐hold duration.…”
Section: Chest Volume Shrinkage and Metabolic Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Increasing metabolic rate also shortens breath‐hold duration (Rodbard, 1947; Cummings, 1962; Lin et al 1974; Ward et al 2001). Figure 4 shows that exercise (bicycle ergometry to at least double metabolic rate) more than halved breath‐hold duration.…”
Section: Chest Volume Shrinkage and Metabolic Ratementioning
confidence: 99%
“…Neither ‘involuntary’ breath‐holding (e.g. central apnoea or suffocation) nor the sensation of breathlessness/air hunger/dyspnoea (Banzett et al 1990; Ward et al 2001) are considered because their precise relationships to the breakpoint are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a high blood lactate (>4 mmol/l), a low alveolar O 2 pressure (<30 mmHg), and a high alveolar CO 2 pressure (>50 mmHg) were registered at the breath-hold breaking in extreme divers by Ferretti (2001). Ward et al (2001) demonstrated that a dyspnoeic sensation has an important role in the length of the BHT during dynamic exercise. They found an exponentially increasing dyspnoeic sensation at a progressively increasing work rate.…”
Section: Discussionmentioning
confidence: 93%
“…Alternatively, the observed effect may be an illustration of the influence of attention on symptom reporting: in the waiting room, patients had nothing to do and could focus their attention on their bodies while they were filling out the questionnaires. During the histamine provocation, there was a lot of equipment in the room and a lot of 'things to do' (inhaling substances, lung function measurements, symptom reports), diverting attention from their internal sensations (Bauldoff, Hoffman, Zullo, & Sciurba, 2002;Ward, Macias, & Whipp, 2001). Some authors doubt the validity of bronchial provocation tests as a laboratory substitute for real life asthma attacks.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to patients who did not use music as a distracter: the latter could not maintain post-pulmonary rehabilitation program gains (Bauldoff, Hoffman, Zullo, & Sciurba, 2002). Ward, Macias, and Whipp (2001) suggested that even exercise per se could serve as an attention-diverting mechanism, thereby influencing the perception of dyspnea.…”
Section: Cue Competitionmentioning
confidence: 93%